1986
DOI: 10.3181/00379727-181-42239
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin Inactivating Activity of Rat Serum

Abstract: The ability of rat serum to inactivate endotoxin (LPS) was assessed with the aid of the limulus amebocyte lysate assay. Following the addition of various amounts of endotoxin to normal serum the mixture was incubated for 1 hr at 37°C and the residual endotoxin activity determined. One milliliter of rat serum inactivated between 5 and 10 pg Escherichia coli LPS per hour. Heating serum for 45 min at 56°C resulted in loss of 80-90% of the LPS inhibitor (LPSI) activity. Serum from cobra venom factor (CVF)-treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…This report attempts to quantitate and characterize endotoxin neutralization to monitor immune system activation in response to Gram-negative bacterial exposure and then test that system in patients with IBD. Consistent with previous reports, we found that a purified endotoxin stock was almost completely (>99%) neutralized after incubation in plasma for 10 minutes [22]. Heating the plasma prior to endotoxin addition decreased the level of neutralization significantly, suggesting that heat-labile factors, such as IgM and enzymatic activity, were responsible for a portion, but not all of the neutralization [20].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This report attempts to quantitate and characterize endotoxin neutralization to monitor immune system activation in response to Gram-negative bacterial exposure and then test that system in patients with IBD. Consistent with previous reports, we found that a purified endotoxin stock was almost completely (>99%) neutralized after incubation in plasma for 10 minutes [22]. Heating the plasma prior to endotoxin addition decreased the level of neutralization significantly, suggesting that heat-labile factors, such as IgM and enzymatic activity, were responsible for a portion, but not all of the neutralization [20].…”
Section: Resultssupporting
confidence: 90%
“…It has been well established that there are components in mammalian blood that neutralize endotoxin [2022]. This report attempts to quantitate and characterize endotoxin neutralization to monitor immune system activation in response to Gram-negative bacterial exposure and then test that system in patients with IBD.…”
Section: Resultsmentioning
confidence: 99%